Online shopping styles of Millennials and Generation Z: Evidence from Indonesia - Arief Helmi; Yogi Suherman; Wa Ode Zusnita (Innovative Marketing)
This study aims to characterize the online shopping style of the young consumer in Indonesia. The study’s primary data were gathered through a survey of 410 Generation Z and Millennial respondents conducted in Bandung, Indonesia in 2024. The data were subjected to factor analysis. According to the survey, both generations prefer to shop online for food, clothing, technology, and personal care products This study discovered three unique online shopping styles for the young generation: fashionable and smart, premium product orientation, and impulsive. The first style represents the young consumer, who enjoys shopping online while seeking contemporary products that save money. Meanwhile, premium product consumers seek high-quality or branded products online, this young consumer buys online seeking exclusivity. The third type is the youthful consumers who commonly purchase online spontaneously without careful review and planning, and regard internet shopping as entertaining. The finding fills the gap in understanding customer behavior, particularly the online shopping style of young consumers. AcknowledgmentWork by the authors was funded by a research grant from the Universitas Padjadjaran [University of Padjadjaran], Indonesia.